Development of Artificial Intelligence-Based Learning Videos on Tayammum Materials (Expert Validation Analysis and Student Response) - Khoirul Umam; Halimatus Sa’diyah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aimed to develop an Artificial Intelligence-based instructional video on tayammum material, examine its feasibility through expert validation, and describe students' responses after using the product. This study employed Research and Development using the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The product was a 3-minute and 16-second instructional video covering the definition, requirements, pillars, causes, procedures, and invalidating factors of tayammum. ChatGPT was used to design prompts and learning scenes, Google Flow was used to generate images and short video scenes, and CapCut was used to edit the final video. The limited trial involved 17 seventh-grade MTs students at PP. Kiai Mudrikah Talang Siring. The expert validation result reached 80.15%, categorized as valid and feasible with minor revisions. The students' response reached 88.09%, categorized as very good. These findings indicate that the AI-based instructional video is feasible as a visual learning medium for Islamic Education, especially for practical fiqh material.